Potential of plant species for bioremediation of soils applied with imidazolinone herbicides - Galon,L. (2014)
Imidazolinone herbicides present physicochemical characteristics that allow them to persist longer in environment, with increased chances of soil and water contamination, as well as carryover effects on subsequent crops. Phytoremediation is shown as a promising technique to decontaminate soils polluted by herbicides. The aim of this study was to assess the potential of some winter grown species in removing residuals from soils contaminated with imazethapyr + imazapic and imazapic + imazapyr, using pre-emergence to control weeds in summer grown rice fields. The experiment was conducted in a completely randomized design, with four replications. All species were subjected to herbicide application at different doses. Imazethapyr + imazapic and imazapyr + imazapic were applied at doses of 0.0, 1.0 and 2.0 L ha-1, and 0.0, 140 and 280 g ha-1, respectively, in pre-emergence of the species. Brassica napus and Festuca arundinaceae are not tolerant to herbicides, with 100% of phytotoxicity (plant death) for all doses assessed. The herbicide imazapyr + imazapic proved to be less selective, causing the highest phytotoxicity in the species tested. The most tolerant species to the herbicides was Vicia sativa, which may be the most suitable one for phytoremediation programs in areas contaminated with imazethapyr + imazapic and imazapyr + imazapic.